Assessing Preference in a Paired-Stimulus Arrangement with Captive Vultures (Aegypius Monachus). Issue 4 (2nd October 2022) - Slocum, Sarah K.; Morris, Kristen L.
ABSTRACT: Vultures play an important role in our ecosystem by filtering out bacteria and viruses harmful to humans (e.g., rabies, botulism). However, many vultures remain in human care due to skill deficits and behavioral excesses, which can be treated using behavior-management practices that rely on effective (often edible) reinforcers. The current study replicated the forced-choice or paired-stimulus preference assessment with five birds of prey. Across all vultures, participants displayed a preference for animal (e.g., meat) over nonanimal stimuli (e.g., fruit), and mice meat was the most preferred edible for 4 of the 5 vultures. The application of this methodology to birds of prey might allow rehabilitators, conservationists, and other caretakers to make greater gains in training vultures to both acquire new skills and decrease problem behavior using highly preferred edible items.